COLONIAL CONQUEST AND THE COLLAPSE OF GAMBARI MARKET IN ILORIN EMIRATE, 1850-1960 (LAPAI JOURNAL OF NIGERIA HISTORY, 2023)
Since 1850s Ilorin was described as one of the greatest entrepots of central Africa and the commercial emporium of all southern Sudan. 1 The town has also been acknowledged for ubiquitous markets located in different parts of the town especially in front of traditional ruler’s houses which served as the commercial centres where goods change hands. This fact is substantiated by Jimoh as cited in 1921 Gazetteer of Ilorin province that: “the most striking feature to a stranger, visiting Ilorin for the first time is the size of its markets”2. The Gambari market was one of the international markets in the pre-colonial Ilorin Emirate, which European explorers and missionaries like Bower, Campbell, Crowder and others have acknowledged. The reason was that foreign and local goods as well as slaves were traded in the Market. The traders from the north and south of the Niger converged in the Market for the exchange of goods and services. Food items from the southern areas of Abeokuta, Ibadan, Osogbo,and Ekiti were traded in exchange for goods like: imported clothes, lanterns, pieces of jewelry, ornaments, horse girdle, and animals such as horse, cow and so on, However, the Gambari market began to decline after the heavy bombardment of Ilorin town by the forces of the Royal Niger Company in 1897, coupled with subsequent integration of the economy of the town into the metropolitan economy. Thischange in the economic system spelt doom for the Gambari market traders as they found it difficult to adapt to the changing business pattern. In view of the foregoing, the paper intends to examine the effects of colonial conquest on the collapse of the Gambari market. It will be study within the context of economic damages which the bombardment had done to the traders, revenue loss on the part of the aristocrats and economic disempowerment of the middlemen. The qualitative research method was adopted for the study, which included oral interviews and secondary sources.